+COMPARATIVE ACCOUNT OF GROWTH RATE 0f BODY PARTS WITH TOTAL LENGTH IN ADULT PUNTIUS SARANA (HAM.) - KUMAR, S.; DUTT, S. (Journal of Indian Fisheries Association, 2015)
The present study on growth rate of different body pa ts in relation to total length, in the male and female Puntius sara.na (Ham.) did not show any significant heterogeneity except in snout length (p.Ol). The growth rate of snout length was found to be higher in females (b 0.0377) than in males (b=0.0266). Since the growth rate of most of the body parts was found to be homogeneous in both the sexes, the common regression co-efficient ’’b" were calculated on pooled data to represent the growth rate of different body parts against total length, The linearity of regression lines indicated isomertirc growth. Keywords: Growth rate, Puntius, morphometry